Field Experiments on Bioelectricity Production from Lake Sediment Using Microbial Fuel Cell Technology - Hong, Seok Won; Kim, Hyung Joo; Choi, Yong Su; Chung, Tai Hak (WILEY-V C H VERLAG GMBH, 2008)
Since particular bacteria are able to oxidize organic matter under anaerobic conditions with concomitant electricity generation while an electrode is serving as an electron acceptor in a fuel cell environment, microbial fuel cells (MFCs) have recently received significant attention. Prototype sediment MFCs were placed in a shallow hypereutrophic lake and generated current for over six months. During the experimental period, a higher electrical current density with an average of 20.4 mA/m(2) was produced using electrodes with higher specific surface areas. Furthermore, parallel connection of sediment MFCs increased the current output. The results showed that current production was severely dependent on temperature and dissolved oxygen concentrations at the cathode. Other findings of this study include not only the direct coupling of current production with a decrease in the organic matter content of the sediment, as well as high positive redox potentials (> +120 mV vs. SHE) in the vicinity of the active anode as compared to sediments where electrodes were not embedded. This implies that the electrochemically active anode evidently acted as an alternative electron acceptor in the sediment, which likely decreased the activity of methanogens and improved the overall decrease in organic matter of sediment. Consequently, this study suggests that the sediment MFC could provide a means for the bioremediation of organic-rich sediment via anaerobic oxidation in conjunction with current production.